2022
DOI: 10.1007/s11136-022-03222-y
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life of Australians during the 2020 COVID-19 pandemic: a comparison with pre-pandemic data and factors associated with poor outcomes

Abstract: Purpose Compare the health-related quality of life (HRQL) of the Australian general population during the COVID-19 pandemic (2020) with pre-pandemic data (2015–2016) and identify pandemic-related and demographic factors associated with poorer HRQL. Methods Participants were quota sampled from an online panel by four regions (defined by active COVID-19 case numbers); then by age and sex. Participants completed an online survey about their HRQL [EORTC QLQ-C3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…It is possible that CR clinicians in our national sample were more aware of quality of life and thus the value of collecting this data. This is following the challenges of the pandemic in 2020, with much discussion and research around the quality of life of Australians after restrictions and lockdowns [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that CR clinicians in our national sample were more aware of quality of life and thus the value of collecting this data. This is following the challenges of the pandemic in 2020, with much discussion and research around the quality of life of Australians after restrictions and lockdowns [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Logits produced congruent results, indicating that these same participants were 1.78 and 2.72 times more likely to experience a reduction in HSU exceeding the 0.08 MID, before to during the pandemic. Supporting this, an Australian general population study (n≈1900) also identified a substantial reduction in HRQoL between before and during pandemic study samples [27]. Additionally, 44.0% of participants were categorised as experiencing minor or major adversity on the composite scale, and 34.0% were identified as having experienced a clinically meaningful reduction in HSU.…”
Section: Associations Between Hsu and Covid-19-related Adversitymentioning
confidence: 70%
“…Today, there is a vast majority of reports about the early effects of the pandemic on the societal and the individual level [ 23 , 24 , 25 , 26 ]. A decline in health-related QOL has been reported for the general population [ 45 , 46 ] as well as for vulnerable subgroups such as cancer patients [ 31 , 47 , 48 , 49 ]. In line with these reports, we observed that ‘emotional functioning’ is the QOL aspect with the highest proportion of need for supportive care during the pandemic era.…”
Section: Discussionmentioning
confidence: 99%